Motivating the multicultural student - Michelle (Mica) Allan (2011)
This study explores how multicultural students in Iceland are motivated to attend further education and what drives their attendance and participation in school. Qualitative research and semi-structured interviews were used to explore this area. Four female students and four male students from different cultures were interviewed. These were all students at The Multicultural School, one of eleven schools which make up The Technical College, Reykjavík (hereafter referred to as The Technical College). Of these eight students, six students were between the ages of 17-20. This age group was specifically chosen for young adults have both the choice and the responsibility for continuing in education rather than attending school by law. Contrastingly, two students in their 30s were interviewed to explore their motivation in pursuing education. In addition four Icelandic teachers were also interviewed. Data from the interviews was analysed using a theory of goal acquisition (Ford, 1992) and explores the students‘ drivers of motivation. In exploring the role of goals in motivation Ford identifies a taxonomy of 24 goals across six categories. These categorical goals have specific relevance when considering that their pursuit and achievement can be even more of a challenge to an individual living and learning in a culture that is not their own. Bronfenbrenner’s model of social ecology (1977) and the many worlds in which individuals operate are also explored in discussing the experiences of the multicultural students. Findings from the thesis have the potential to impact on school curriculum, school policy and national educational policy regarding multicultural students within Iceland. Key findings include that younger students are more motivated by social and collaborative goals, students with an older outlook are more motivated by cognitive development goals and that multicultural students are influenced by and inhabit many different worlds.